Efferocytosis drives myeloid NLRP3 dependent inflammasome signaling secretion of IL-1β to promote tumor growth - Lang, Cara; Roy, Sohini; Wang, Yu; Graves, Diana; Xu, Yaomin; Serezani, C. Henrique; Korrer, Michael; Kim, Young J. (Frontiers in Immunology, 2022)
Caspase-1 signaling in myeloid suppressor cells can promote T-cell independent cancer progression, but the regulation of inflammasome signaling within the highly heterogeneous myeloid population in the tumor milieu remains elusive. To resolve this complexity, single cell transcriptomic profile of HNSCC identified distinct inflammasome-associated genes within specific clusters of tumor-infiltrating myeloid cells. Among these myeloid cells, NLRP3 and downstream effector IL-1β transcripts were enriched in discreet monocytic and macrophage subtypes in the TME. We showed that deletion of NLRP3, but not AIM2, phenocopied caspase-1/IL-1β dependent tumor progression in vivo. Paradoxically, we found myeloid-intrinsic caspase-1 signaling increased myeloid survival contrary to what would be predicted from the canonical pyroptotic function of caspase-1. This myeloid NLRP3/IL-1β signaling axis promotion of tumor growth was found to be gasdermin D independent. Mechanistically, we found that phagocyte-mediated efferocytosis of dying tumor cells in the TME directly activated NLRP3-dependent inflammasome signaling to drive IL-1β secretion and promote tumor growth. Dynamic RNA velocity analysis showed a robust directional flow from efferocytosis gene-sethigh macrophages to an inflammasome gene-sethigh macrophage population. We provide a novel efferocytosis dependent inflammasome signaling pathway which mediates homeostatic tumor cell apoptosis that characterizes chronic inflammation-induced malignancy.